The Influence of Customer Brand Engagement on Brand Loyalty Through Brand Trust - Lutfiah, Azizatul; Elistia, Elistia (Journal of Current Research In Multidisciplinary, 2026)
In an era of increasingly fierce business competition, brand loyalty is a crucial factor for the sustainability and success of the company. Brand loyalty can strengthen market position due to consumer trust and engagement. This study aims to analyze the effect of customer brand engagement on brand loyalty through the role of brand trust as a mediating and moderating variable. This research uses a quantitative approach with descriptive causality method. The population in this study are consumers who already know and have bought Cimory milk products who live in Jabodetabek. The sampling method uses non-probability sampling with purposive sampling technique. The sample criteria for this study are age ranging from 17 years - 50 years with the number of samples processed as many as 149 respondents who are consumers of Cimory products in the Jabodetabek area. Data were collected through online questionnaires and analyzed using Structural Equation Model Partial Least Square. The results showed that customer brand engagement has an influence on brand trust and brand loyalty. However, although there is a relationship between customer brand engagement and brand trust, brand trust does not support the moderation of the relationship between customer brand engagement and brand loyalty. This suggests that brand trust is not always the key factor in linking brand loyalty with customer brand engagement, and there may be other factors that are more influential in the process. Therefore, marketing strategies should include a more holistic approach that not only relies on brand trust, but also includes other elements such as customer experience, product quality, and innovation. This research provides insights for companies to focus more on strategies to increase customer engagement to strengthen brand loyalty, and highlights the importance of nurturing customer trust to strengthen the relationship between brand engagement and long-term loyalty.